2020
DOI: 10.1186/s40795-020-00355-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a nutrition education programme on the metabolic syndrome in type 2 diabetes mellitus patients at a level 5 Hospital in Kenya: “a randomized controlled trial”

Abstract: Background Type 2 diabetes mellitus (T2D), is a life-threatening condition of global public health concern. It worsens in the presence of the metabolic syndrome (MetS), a complex disorder characterized by co-occurrence of at least three of such factors as hypertension, obesity, dyslipidemia and insulin resistance. However, lifestyle interventions reduce the risk of both MetS and T2D, and nutrition education can empower individuals on the appropriate, lifestyle changes. The aim of the current study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(54 citation statements)
references
References 44 publications
6
47
0
1
Order By: Relevance
“…Nutrition education programs conducted in other countries have shown the effectiveness of this method in reducing some MetS risk factors [ 43 , 44 ]. In our study, lower waist circumference, fat mass, fasting glucose, total cholesterol, and LDL-cholesterol and higher HDL-cholesterol showed post-intervention in the INEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition education programs conducted in other countries have shown the effectiveness of this method in reducing some MetS risk factors [ 43 , 44 ]. In our study, lower waist circumference, fat mass, fasting glucose, total cholesterol, and LDL-cholesterol and higher HDL-cholesterol showed post-intervention in the INEG.…”
Section: Discussionmentioning
confidence: 99%
“…A longer study period is recommended to demonstrate long-term effects. However, the study period of 2–3 months is typical for this type of study [ 36 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Greece have revealed suboptimal nutrition knowledge among patients with DM [24][25][26], highlighting the need for an integrated approach to patient education. In parallel, randomized controlled trials (RCTs) have unanimously revealed improvements in glycemic control and disease prognosis following the implementation of nutrition education sessions [27,28]. In a study conducted in the USA [29] (Table 4), patients with T1DM and T2DM were educated on nutritional issues by an RDN and set individual goals based on the ADA/Morrison Health Care (MHC) recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were randomised controlled trials (RCTs) [16][17][18][19][20][21][22][23][24][25], followed by pre-post design [26][27][28][29][30][31][32] (Table 1). Five interventions were conducted in the United States [17,18,26,[29][30][31][32].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven studies were conducted among adults with MetS or at risk for the syndrome without other medical conditions [16][17][18]24,27,28,30,33]. Three studies were conducted among adults with other medical issues and increased risk for MetS [25,29,31,32], while two interventions were conducted among obese adults [19,20,23]. National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III (NCEP ATP III) criteria were the most commonly used MetS definition for patient inclusion [16,[21][22][23]26], followed by International Diabetes Federation (IDF) [17][18][19][20] and Joint Interim Societies (JIS) Harmonised criteria [27,28].…”
Section: Study Characteristicsmentioning
confidence: 99%